Evaluation of Available Online Information Regarding Treatment for Vitreous Floaters - Kalavar, Meghana (Semin Ophthalmol, 2021)
OBJECTIVE: To assess the quality, content, and readability of information available online on vitreous floater information. DESIGN: Cross-sectional study. PARTICIPANTS: Not applicable METHODS: Websites were generated using a Google search of “vitreous floaters treatment” and “[State]” and were analyzed using a standardized checklist of 22 questions. Readability was assessed using the Flesch Reading Ease score. Websites met qualification criteria if they represented U.S. based institutions, if they provided clinical care and addressed vitreous floater treatment on their website. RESULTS: Of the 1,065 websites screened, 456 were included. Of these, 406 (89%) were private institutions, 24 (5.3%) were academic, and 26 (5.7%) were a combination of private and academic. The average readability score correlated to a 10th-12th grade reading level. Vitreous floater treatment was discussed on 283 (62.1%) websites and 63 (21.8%) websites discussed potential side effects. Google rank was inversely correlated with depth of explanation (r= −0.114, p=.016). Observation was the main treatment recommended (55.8%, n=158), followed by laser treatment (27.6%, n=78), no specific treatment recommendation (11.3%, n=32), and vitrectomy (5.3%, n=15). Centers with vitreoretinal surgeons were 16.43 times more likely to recommend vitrectomy than those without vitreoretinal surgeons (p<0.001). CONCLUSIONS: Online information about vitreous floater treatment is variable, and the material is at a higher than recommended reading level for health information. While treatment was discussed by nearly two thirds of websites, less than a quarter mentioned possible complications, and treatment recommendations varied significantly depending on physician training.